Cultural Innovation Ulos Design to Promote Tourism Ulos Batak in Toba - Jessica Ignatia Tambunan; Apriliani Lase (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2023)
Ulos is traditional Batak clothing and found only during traditional ceremonies but with the current generation who are increasingly forgetting the culture for ulos development. Using case study and idea of ulos cultural innovation design with motifs found from goods that can be carried anywhere by the wearer. And not only Batak people who use ulos. The purpose of this study is to identify cultural innovation ulos design will promote tourism ulos Batak in Toba. Ulos design innovation has had the effect of developing Lake Toba and promote as a tourist destination for ulos locations.